(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2019)
Da"wah work was one of the main means that helped spread Islam throughout the Malay Archipelago. The advent of Islamic resurgence in 1970s that came along with the emergence of influential Islamic movements had transformed the da?wah work to become more sophisticated. This paper attempts at understanding the relationship between the traditional da?wah work and the Islamic movements in Malaysia before looking in-depth at the development of Islamic movements in establishing and improving da?wah methodology and institutions. Findings reveal that the Islamic movements played a very significant role in reforming da?wah work. They had introduced an alternative system in da?wah work that had been manifested either in their own private institutions or through advocacy of da?wah work policies as well as in its implementation within the existing da?wah work. The findings also prove that the differences in political ideology were not a major obstacle for them in developing da?wah work in the country. In conclusion, despite the varied understanding and approach of Islamic movements, their contribution in developing the nation through da?wah work is significant. Overall, the Islamic movements now have to improve the quality of their da?wah work and learning process in order to face current challenges and obstacles.